Snow White and the Seven Dwarfs: a fairytale for endocrinologists. Issue 5 (19th May 2021) - Zervas, Athanasios; Chrousos, George; Livadas, Sarantis
Abstract : 'Snow White and the Seven Dwarfs', a fairytale that is widely known across the Western world, was originally written by the Brothers Grimm, and published in 1812 as 'Snow White'. Though each dwarf was first given an individual name in the 1912 Broadway play, in Walt Disney 's 1937 film 'Snow White and the Seven Dwarfs', they were renamed, and the dwarfs have become household names. It is well known that myths, fables, and fairytales, though appearing to be merely children's tales about fictional magical beings and places, have, more often than not, originated from real facts. Therefore, the presence of the seven brothers with short stature in the story is, from an endocrinological point of view, highly intriguing, in fact, thrilling. The diversity of the phenotypes among the seven dwarfs is also stimulating, although puzzling. We undertook a differential diagnosis of their common underlying disorder based on the original Disney production's drawings and the unique characteristics of these little gentlemen, while we additionally evaluated several causes of short stature and, focusing on endocrine disorders that could lead to these clinical features among siblings, we have, we believe, been able to reveal the underlying disease depicted in this archetypal tale.